Peripheral oxytocin suppresses food intake and causes weight loss in diet-induced obese rats - Morton, Gregory J. (American Physiological Society, 2012)
Growing evidence suggests that oxytocin plays an important role in the regulation of energy balance and that central oxytocin administration induces weight loss in diet-induced obese (DIO) animals. To gain a better understanding of how oxytocin mediates these effects, we examined feeding and neuronal responses to oxytocin in animals rendered obese following exposure to either a high-fat (HFD) or low-fat diet (LFD). Our findings demonstrate that peripheral administration of oxytocin dose-dependently reduces food intake and body weight to a similar extent in rats maintained on either diet. Moreover, the effect of oxytocin to induce weight loss remained intact in leptin receptor-deficient Koletsky (fa(k)/fa(k)) rats relative to their lean littermates. To determine whether systemically administered oxytocin activates hindbrain areas that regulate meal size, we measured neuronal c-Fos induction in the nucleus of the solitary tract (NTS) and area postrema (AP). We observed a robust neuronal response to oxytocin in these hindbrain areas that was unexpectedly increased in rats rendered obese on a HFD relative to lean, LFD-fed controls. Finally, we report that repeated daily peripheral administration of oxytocin in DIO animals elicited a sustained reduction of food intake and body weight while preventing the reduction of energy expenditure characteristic of weight-reduced animals. These findings extend recent evidence suggesting that oxytocin circumvents leptin resistance and induces weight-loss in DIO animals through a mechanism involving activation of neurons in the NTS and AP, key hindbrain areas for processing satiety-related inputs.